Peningkatan Pengetahuan Remaja tentang Stunting melalui Edukasi Interaktif di Sekolah - Reny Eka Saputri; Mutiarawati Mutiarawati; Meyliya Meyliya (Jurnal Surya Masyarakat, 2025)
Stunting is a chronic health problem due to long-term lack of nutritional intake that affects childrens growth and development, both physically and cognitively. Prevention of stunting is not only focused on toddlers, but must start from adolescence as future mothers and fathers. Unfortunately, teenagers knowledge about stunting is still relatively low. This community service activity aims to increase adolescents knowledge about stunting through interactive educational methods in schools. The methods used were participatory lectures, group discussions, interactive quizzes held at SMAN 1 Pangkah, Tegal Regency. A total of 48 grade X students were involved as respondents. Evaluation was conducted through pre-test and post-test to measure the increase in knowledge. The results showed an increase in the average score of knowledge from 58,2 (pre-test) to 83,7 (post-test). In addition, participants showed high enthusiasm during the activity, indicated by active participation in discussion and question and answer sessions. Interactive education is proven to be more effective in improving adolescents understanding than conventional methods because it is able to create a fun learning atmosphere and build a sense of belonging to health issues. This activity shows that school-based stunting education with an interactive approach can be a targeted preventive strategy and needs to be replicated in other schools. It is hoped that similar activities can contribute to reducing stunting rates through increasing awareness from adolescence.